Inhibitory Effect of Ruta graveolensL. Extract on Guinea PigLiverand Bovine Milk Xanthine Oxidase: Inhibitory effect of Ruta graveolenson xanthine oxidase - Saeed Pirouzpanah,; Mohammad R. Rashidi,; Abbas Delazar,; Seyed Vali Razavieh,; Ali Asghar Hamidi, (Iranian Journal of Pharmaceutical Sciences, 2009)
Flavonoids could serve as potent inhibitors of xanthine oxidase (XO). In the present study, the effects of Ruta graveolensL. extract and its major isolated flavonoids,quercetin and rutin, on guinea pig liver XO have been investigated. The inhibitory effects of R. graveolens, quercetin and its glycoside form, rutin, were assayed spectrophotometrically. R. graveolensextract showed moderate inhibition on XO activity. Interestingly, bovine milk and guinea pig liver XO were inhibited significantly at different ranges by either the extract or its flavonoids, whereas allopurinol acted with almost the same potency on both enzymes. Rutin inhibited the enzymes in a competitive manner, while quercetin was found to be a competitive and mixed inhibitor of guinea pig liver and bovine milk XO, respectively. In conclusion, R.graveolensextract can act as a good inhibitor of XO. Interestingly, it was shown that the inhibitory effects of flavonoids on XO could be species dependent.